Dipole plasmon vitalized efficient white light emission via charge transfer in all oxide-based heterojunctions. (1st July 2023) - Sumanth, Arige; Mishra, Vikash; Singh, Vipul; Rao, M.S. Ramachandra; Dixit, Tejendra
Abstract: Solid-state white-light emission, which is rapidly becoming the standard in a wide range of lighting applications, can be regarded as the best possible light source for next-generation cost-effective lighting. Herein, we report a simple solution-based technique to get efficient white-light emission using all-oxide semiconductor-based heterojunction. In this work, vertically oriented CuO nanorods were used for outstanding white-light emission by depositing ZnO thin films over CuO nanorods. The resulted bi-layered ZnO/CuO heterojunction arrangement have shown excellent optoelectronic properties. Furthermore, the inclusion of Au layer between ZnO/CuO heterojunction has improved white-light emission significantly and as an integral, a white light photoluminescence (PL) with a chromaticity coordinate of (0.32, 0.34) was obtained. Ab-initio calculations have supported our mechanism of charge transfer from CuO to ZnO especially with Au insertion. The presented work will provide insights into the intriguing optoelectronic properties of oxide hetero-structures. Graphical abstract: Image, graphical abstract